ABOUT ACCOUNT OF VIBRATION SPEEDS AT MILLING SPARS - O.A. KALASHNIKOVA (Advanced Engineering Research)
Process of formation of vibrations in-process surveyed at milling lengthy details (spars). Analytical dependences which allow to calculate a spectrum of vibrations of the spar are obtained and on this basis to define expected levels of emitted noise.